The Relative Productivity Hypothesis of Industrialization: The American Case, 1820 to 1850 - Goldin, Claudia; Sokoloff, Kenneth (Quarterly Journal of Economics, 1984)
A two-sector model is used to explore the role of the agricultural sector in the process of industrialization. Our hypothesis is that areas industrialize earlier where the wages for females and children relative to those for adult males are initially low. Furthermore, the lower this relative productivity of females and children in the pre-industrial economy, the proportionately more will their relative wages increase, and the higher will be the ratio of manufactured to agricultural goods. The model is used to interpret the conditions that fostered the rapid industrialization of the American Northeast, but not the South, from 1820 to 1850.